Depresión y consumo de drogas legales en los estudiantes de la Unidad Educativa Marieta de Veintimilla, ciudad de Loja, periodo 2021 - Iñiguez Sozoranga, Diego Armando (2022)
Nowadays it’s common to observe adolescents with symptoms of depression caused by multiple emotional, family, environmental and social problems that often cause "escape" behaviors such as the consumption of psychoactive substances. With this background, the present investigation established if there is a relationship between depression and drug use in the students of a School in the city of Loja. The research was correlational, descriptive and exploratory, carried out on 128 students. Psychometric instruments were used like the Beck Depression Inventory and the Test for the detection of alcohol, tobacco and substance use. Through this study it was determined that the level of depression which most of the students present is minimal, in the same way, it was evidenced that a considerable quantity of the students have consumed alcohol, but in terms of tobacco consumption the majority of students do not consume it. Therefore, it was established that there is no relationship between depression and legal drug use, this indicates that legal drug use is not influenced by depression